Age-related differences in food-specific inhibitory control: Electrophysiological and behavioral evidence in healthy aging. (1st April 2023) - Allen, Whitney D.; Carbine, Kaylie A.; Clayton, Colter K.; LeCheminant, James D.; Larson, Michael J.
Abstract: The number of older adults in the United States is estimated to nearly double from 52 million to 95 million by 2060. Approximately 80–85% of older adults are diagnosed with a chronic health condition. Many of these chronic health conditions are influenced by diet and physical activity, suggesting improved diet and eating behaviors could improve health-related outcomes. One factor that might improve dietary habits in older adults is food-related inhibitory control. We tested whether food-related inhibitory control, as measured via behavioral data (response time, accuracy) and scalp-recorded event-related potentials (ERP; N2 and P3 components), differed between younger and older adults over age 55. Fifty-nine older adults (31 females [52.5%], M age  = 64, SD age  = 7.5) and 114 younger adults (82 females [71.9%], M age  = 20.8) completed two go/no-go tasks, one inhibiting to high-calorie stimuli and one inhibiting to low-calorie stimuli, while electroencephalogram (EEG) data were recorded. Older adults had slower overall response times than younger adults, but this was not specific to either food task. There was not a significant difference in accuracy between younger and older adults, but both groups' accuracy and response times were significantly better during the high-calorie task than the low-calorie task. For both the N2 and P3 ERP components, younger adults had larger no-go ERP amplitudes than older adults, but this effect was not food-specific, reflecting overall generalized lower inhibitory control processing in older adults. P3 amplitude for the younger adults demonstrated a specific food-related effect (greater P3 amplitude for high-calorie no-go than low-calorie no-go) that was not present for older adults. Findings support previous research demonstrating age-related differences in inhibitory control though those differences may not be specific to inhibiting towards food.